2022
DOI: 10.3390/s22103791
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic Cantilevers Containing a Magnetoactive Elastomer: Magnetoelectric Response to Low-Frequency Magnetic Fields of Triangular and Sinusoidal Waveform

Abstract: In this work, multiferroic cantilevers comprise a layer of a magnetoactive elastomer (MAE) and a commercially available piezoelectric polymer-based vibration sensor. The structures are fixed at one end in the horizontal plane and the magnetic field is applied vertically. First, the magnetoelectric (ME) response to uniform, triangle-wave magnetic fields with five different slew rates is investigated experimentally. Time and field dependences of the generated voltage, electric charge, and observed mechanical def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…A two-layered structure composed of PVDF and magnetic elastomer was investigated earlier [29][30][31][32][33]. The initial experiments of the magnetoelectric effect were carried out in a pulsed magnetic field of different forms oriented transversally [29][30][31]. Such a configuration is also called T-T [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A two-layered structure composed of PVDF and magnetic elastomer was investigated earlier [29][30][31][32][33]. The initial experiments of the magnetoelectric effect were carried out in a pulsed magnetic field of different forms oriented transversally [29][30][31]. Such a configuration is also called T-T [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was proven that the higher the mass fraction of magnetic particles as long as the thickness of MAE layer, the larger the ME effect that could be obtained [29,30]. In one work [31], it was found that value sinusoidal excitation is more effective than triangular. The authors of articles [29][30][31] suppose that the ME effect originates owing to a gradient in the magnetic field inside the MAE layer.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic elastomers are one of the stimulus-responsive soft materials, i.e., materials whose physical properties change in response to magnetic fields, e.g., macroscopic expansion and contraction under gradient magnetic fields, magnetostriction, rotational motion under rotational magnetic fields, magnetorheological greases, multiferroic cantilevers, adhesion and friction properties due to magnetic switching, tunable vibration–absorption, and variable surface microstructure. , Magnetic elastomers consisting of polymer matrix and magnetic particles generally undergo a large magnetic response and are expected to be practical actuators. When a magnetic field is applied to a magnetic elastomer, the elasticity increases due to the formation of a chain-like structure of the magnetic particles (restructuring), known as the magnetorheological (MR) effect.…”
Section: Introductionmentioning
confidence: 99%
“…The state of theoretical studies of MAEs is discussed at length in [ 7 , 11 , 23 , 24 ]. The interest surrounding MAEs is driven by their potential applications in civil engineering as vibration dampers, remotely controlled switches, and noise control systems [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], in soft robotics as actuators [ 13 , 14 , 32 , 33 , 34 ], in entertainment as parts of haptic feedback devices [ 15 , 35 , 36 , 37 ], in biomedical devices as adaptive compressors and seals [ 38 , 39 , 40 , 41 , 42 ], in communication systems as microwave and radio frequency filters [ 43 , 44 , 45 ], and in automobile production as active braking systems [ 46 , 47 , 48 ]. Historically, the majority of both fundamental and applied research concerning MAEs has centered on harnessing the bulk properties of these materials.…”
Section: Introductionmentioning
confidence: 99%